Estrutura da Comunidade de Fungos Endofíticos eBioprospecção de Isolados de Aspilia grazielae (Santos), Espécie Vegetal Endêmica de Mato Grosso do Sul - Carlos Eduardo Weirich (2020)
The use of new technologies for stuying DNA has been growing over the last recent years. These changes began in 2005 with the emergence of the pioneering technologies known as NGS (Next Gen Sequencing), allowing a new approach to large-scale sequencing. These new technologies promote DNA sequencing on platforms capable of generating information on millions of base pairs. In this work, we used the Illumina MiSeq platform to investigate and compare the community structure of endophytic fungi of Aspilia grazielae. We also used the method of plating plant fragments (leaves and roots) in BDA medium to isolate endophytic fungi in vivo. This work was divided into three chapters which address aspects related to the community structure of endophytic fungi and their biotechnological potential for bioremediation and bioprospecting. It was investigated how mining influences the community of endophytic fungi from plants grown in two areas, a native and a recovery area (Chapter 1), the biotechnological potential for bioremediation of Fe+2 and Mn+2 by the fungi that showed greater tolerance and these metals (Chapter 2), and the ability of three isolates of the Aspergillus genus to promote the growth of Aspilia grazielae seedlings (Chapter 3). According to the results of Chapter 1, we found a significant reduction in the phylum of Ascomycota in the recovery area, indicating a great impact of the anthropogenic process in this community. Therefore, although our study is a snapshot of this complex community, we suggest the importance of preserving the native area of the Pantanal massifs, not only to conserve the biodiversity of mycobiota but also as a source of rhizosphere endophytic community to colonize areas of activity recovery mining companies that could be instrumental in the success of recovery initiatives. In Chapter 2, in which we evaluated the potential for bioremediation by isolates the genus Aspergillus and Penicillium, we found that the genus Aspergillus was more tolerant to the metals tested as the genus Penicillium. However, for the bioremediation purposes, Aspergillus isolate. Among all tested isolates, an isolate of the genus Penicillium (CR1) proved to be the most efficient for removing mainly Fe+2. The result indicates the potential for applicability of the CR1 strain for the remediation of heavy metals from polluted soils and waters. In Chapter 3, the results convey the ability of Aspergillus isolates to grow in culture medium comprising concentrated solutions of Fe+2 and Mn+2. It was also observed that the isolates when added to the soil, promoted the vegetative growth of A. grazielae seedlings, acting as growth biostimulators, with potential to act as biofertilizers in sustainable agriculture programs. However, further studies are needed to propose the preparation of a growth-inducing bioformulation and, to reveal the mechanisms by which these fungi act.